If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + -6X = 10 + -10 Combine like terms: 10 + -10 = 0 -14 + -6X = 0 Solving -14 + -6X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -6X = 0 + 14 Combine like terms: -14 + 14 = 0 0 + -6X = 0 + 14 -6X = 0 + 14 Combine like terms: 0 + 14 = 14 -6X = 14 Divide each side by '-6'. X = -2.333333333 Simplifying X = -2.333333333
| q+13=112 | | 4X-7=56-3 | | (3/x-2)-(1-x/x) | | 3/x-2-1-x/x | | 12x-8=-3x+7 | | w+19=62 | | 4x-3y=-43 | | 2u^5*2w*7w^9u^9= | | b^2-35=0 | | Y/8+13=17 | | t-20=54 | | X/4+1=101 | | 10abc-4-2a+20bc=0 | | Y/5+2=17 | | X+(x+2)=198 | | 110=s+65 | | 5+4(1+3x)=-16 | | 15-0.5x=0 | | 10-5t=25 | | 25xy^3-50y^3z-15x^2y^2+30xy^2z=0 | | 27-5y=12 | | 9x-4-7x=5x+17 | | -7(9-4c)=-20 | | 3k-8=19 | | 20x^2-45=0 | | 3x+3-x=69 | | 7m-19=30 | | -5(4h+8)=27 | | -71(y-27)=y-93 | | 8+X=13+2 | | 5n-8n=23 | | (3b/4a)+(5c/7a)=2 |